Study on Growth of Rural Non-Farm Employment for Selected District of Haryana - Planning Commission (Planning Commission, 2002)
The two selected districts, one in the western and the other in eastern region of Haryana, show rather different picture of Non-farm employment and its growth between 1997-98 and 2001-2002. The agriculturally advanced Kurukshetra district showed much higher rate of growth of Non-farm employment than Bhiwani - higher than 3-4 percent growth of labour force over the period as per latest NS SO Round.
Planning Commission Government of India
Planning Commission Government of India